‘Oh yeah, yeah you get a lot of love hearts. The Year 9s are notorious for love hearts. Everything is love hearts.’ Fixation in Pupils’ Design and Technology Work (11-16 years) - Nicholl, Bill; McLellan, Ros (Design and Technology Education: An International Journal, 2007)
This paper focuses on the design ideas generated by young people aged 11-16 years when solving design and technology problems. A number of methods including focus interviews with pupils and teachers, lesson observations and analysis of documents and pupils portfolios are used to help explain how pupils aged 11-16 years generate their design and technology ideas. The findings indicate that a significant number of pupils produced stereotypical design ideas such as love hearts and sports logos. This was the case regardless of their age and gender and happens at various stages when designing. A review of the creative cognition literature suggests that this occurs as a result of a normal way of thinking and is referred to as fixation. Fixation, that is, what it looks like and how it manifests itself in the D&T classroom is discussed in detail. Fixation was also found to manifest itself in other ways such as a strong desire to do the first idea that comes into your head. It is argued that an understanding of fixation gives insight into why pupils find it difficult to generate creative design ideas. As fixation can be overridden, we believe that the role of the teacher in this process is important. Aspects of current practice that might be problematic are begun to be considered.